The impact of cleaning on the microbiomes of indoor surfaces - Martin Täubel; Emmanuelle Castagnoli; Tunga Salthammer; Lidia Morawska; Heidi Salonen (Elsevier, 2024)
Research into cleaning agents and disinfectants and associations with human health is typically performed from a chemical or particle exposure perspective. We lack good understanding of how cleaning chemicals and practices affect the microbiomes on indoor surfaces in real-life environments and what that might imply for human exposure and health. The objective of this review was to provide an overview and summary interpretation of studies investigating these aspects. Literature searches were performed using PubMed and Web of Science, limiting the results to studies published between 2013 and 2023. In total, 72 original research papers fulfilled our inclusion criteria and were considered in the data extraction. We found that the literature is dominated by experimental laboratory studies that evaluate and compare cleaning/disinfection efficacy of individual or multiple products or approaches. Such studies are largely motivated by the need to reduce healthcare-associated infections (HAIs) and to respond and prepare to outbreaks and pandemics caused by microbes. Observational studies in real-life environments are less common and report partly contradicting results with respect to the impact of cleaning on surface microbiomes. Promising results from probiotic cleaning and hygiene systems (PCHS) applied to healthcare environments encourage concepts of curating or engineering indoor microbial populations rather than trying to eliminate them. Studies on re-establishment of surface microbiota indicate that efforts to eliminate microbes from indoor surfaces are indeed inefficient, which adds to concerns over promoting antimicrobial resistance and increasing chemical loads indoors due to excessive use of cleaning agents.